Start with the original equation: \[ 6(9y-1) - 10(5y) - 3y = 22 - 4(2y-12) + 8(y-6) \] Expand both sides: \[ 54y - 6 - 50y - 3y = 22 - 8y + 48 + 8y - 48 \]
Combine the terms on both sides: \[ (54y - 50y - 3y) = (22 + 48 - 6) \] This simplifies to: \[ y - 6 = 22 \]
To isolate \(y\), add 6 to both sides: \[ y = 22 + 6 \] Thus, we find: \[ y = 28 \]
\(\boxed{y = 28}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.